O comportamento de uso de internet e sua relação com estilos de autoconsciência em universitários : contribuições da meditação mindfulness e da gestalt-terapia - Nunes, Andrea Loss (2019)
Recent studies on the use of the internet have been pointing, alongside the positive aspects, negative aspects that are related to serious psychological disorders. Considering the impact of information technologies on human behavior, it is reasonable to assume that individual differences in the style of self-awareness and self-regulation capacity are important factors in mediating a more or less healthy relationship between the human being and information technologies, such as internet use Therefore, the general objective of this research is to verify the association between internet use and self-awareness styles and to develop the adaptation of a mindfulness-based meditation program for university students who make moderate use of the internet. Therefore, three sequential studies were proposed, which are presented in three articles format. Article I, entitled "Association between self-awareness and use of the internet in university students", aimed to verify the correlation between the level of internet use and styles of self-awareness of ruminative and reflexive, through a quantitative research with the participation of 450 adult college students, 18 to 25 years of age. The results indicated a significant positive correlation between the level of internet use and self-awareness of rumination. Article II, entitled "Mindfulness Meditation and Internet Use in the Perception of College Students", had the general objective of describing the perception of university students who make moderate use of the internet, about their participation in a program based on the mindfulness meditation technique . It is a qualitative study, following the criteria of analysis of phenomenology-semiotics. Participants were university students (N = 3) of both sexes, selected for convenience, chronological age of 18 to 25 years, who participated in a program based on mindfulness meditation. The results suggested the acceptance of the negative and positive aspects of self as a structuring axis for the controlled use of the internet. Finally, Article III, titled "Meditation mindfulness and Gestalt therapy: a possible encounter for human health", aimed to identify possibilities of theoreticalpractical interlocution between the Mindfulness Meditation technique and the Gestalt-therapy psychological approach. It was sought to identify, compare and contrast the terms that are common to them and concepts found in their respective theoretical-practical frameworks. Although these concepts have their meanings constituted in their different theories, it was possible to identify an interlocution from the design of three integrative axes: (1) integrative self-consciousness, (2) functional self-consciousness and (3) spontaneous self-regulation. The final considerations of the thesis suggest that the uncontrolled use of the internet can be avoided or treated, as there is a globalizing view about the human being. This perspective corroborates the proposal of Mindfulness Meditation and the proposal of Gestalt-therapy clinical psychology, since both point the systemic view as a crucial path for human development in all its aspects.